Does China's low-carbon city pilot policy promote green development? Evidence from the digital industry - Zeyu Wang; Feiyan Liang; Chengming Li; Wenzuixiong Xiong; Yunsi Chen; Fanbao Xie (Journal of Innovation & Knowledge (JIK), 2023)
The low-carbon city pilot (LCCP) policy is an essential strategy for China to combat climate change, attain the carbon neutrality target, and achieve comprehensive green transformation, which will inevitably have an impact on many areas of the economic system. The digital economy has given a new impetus to green development and sustainable growth in China, becoming an essential indicator of green transformation. Promoting the digital economy's growth is essential to successful green development. Does China's LCCP policy support digital economy growth while reducing energy use and emissions? This study evaluates digital economy growth in China's 277 cities from 2002 to 2019 using the principal component analysis method and employing the difference-in-differences method to assess how the LCCP policy affects digital economy growth. The empirical results demonstrate that the LCCP policy encourages digital economy growth, which then promotes green development. The conclusion remains tenable following several robustness tests, including parallel trend, placebo, and endogeneity tests. A heterogeneity analysis demonstrates that the LCCP policy has a more profound influence on digital economy growth in coastal, non-resource-based, and large-scale cities. A mechanism test indicates that the LCCP policy positively encourages digital economy growth by promoting technological innovation and changing the industrial structure. This study offers new empirical evidence that LCCP policy can advance the achievement of green development.
Keywords: E23; G10; G21; 650; DID method; Digital industry; Green development; Industrial structure change; Low-carbon city pilot; Technological innovation